Single Dose Administration of L-Carnitine Improves Antioxidant Activities in Healthy Subjects - Qu, Hai-jun; Han, Zhi-wu; Li, Ping; Wang, Le-xin; Wang, Chun-bo; Cao, Yu (The Tohoku Journal of Experimental Medicine, 2011)
L-carnitine has been used as a supplement to treat cardiovascular or liver disease. However, there has been little information about the effect of L-carnitine on anti-oxidation capability in healthy human subjects. This study was designed to investigate the correlation between plasma L-carnitine concentration and antioxidant activity. Liquid L-carnitine (2.0 g) was administered orally as a single dose in 12 healthy subjects. Plasma concentration of L-carnitine was detected by HPLC. The baseline concentration of L-carnitine was 39.14 ± 5.65 μmol/L. After single oral administration, the maximum plasma concentration (Cmax) and area under the curve (AUC0-∞) were 84.7 ± 25.2 μmol/L and 2,676.4 ± 708.3 μmol/L·h, respectively. The half-life and the time required to reach the Cmax was 60.3 ± 15.0 min and 3.4 ± 0.46 h, respectively. There was a gradual increase in plasma concentrations of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), catalase and total antioxidative capacity (T-AOC) in the first 3.5 h following L-carnitine administration. The plasma concentrations of SOD, GSH-Px, catalase and T-AOC returned to baseline levels within 24 h. A positive correlation was found between L-carnitine concentration and the antioxidant index of SOD (r = 0.992, P < 0.01), GSH-Px (r = 0.932, P < 0.01), catalase (r = 0.972, P < 0.01) or T-AOC (r = 0.934, P < 0.01). In conclusion, L-carnitine increases activities of antioxidant enzymes and the total antioxidant capacity in healthy subjects. It may be useful as a supplementary therapy for chronic illnesses involving excessive oxidative stress.